Calculated estimation of the influence of informality of the fuel spray on the field of gas temperatures at the outlet of the combustion chamber of a GTE - Сергей Анатольевич Евсеев (National Aerospace University «Kharkiv Aviation Institute», 2021)
This paper presents the results of numerical simulation of a gas flow with the combustion of atomized liquid fuel (the equilibrium combustion model pdf was used along with the model of a partially mixed mixture) in an annular combustion chamber of a gas turbine engine. Numerical modeling was carried out in the ANSYS Fluent computational complex. The purpose of the calculations was to assess the influence of the unevenness of the fuel spray specified in the design documentation and the coking of the parts of the front-line device on the radial and circumferential unevenness of the gas temperature field at the exit from the combustion chamber. The simulation used the previously verified turbulence model k-e with the functional dependence of the turbulent Schmidt number Sc on the gas temperature, which was implemented in the ANSYS Fluent computational complex using the user function (UDF). Since the fuel injector and the swirler represent a rather complex spraying scheme, which does not allow calculating the amount of fuel entering through the holes in the swirler cap, an installation was made and tests were carried out to determine the amount of the fuel-air mixture distributed over the holes in the swirler cap. The experimental values of the distribution of the air-fuel mixture through the holes in the swirler cap were further used to perform numerical simulation of combustion in the combustion chamber. Numerical modeling was carried out with sector non-uniformity equal to 0 %, 50 % (the maximum allowable according to the design documentation), and during coking of the swirler cap holes. As a result of the calculations, it was found that the sector irregularity of 50 % has an insignificant effect concerning the sector irregularity of 0 % on the radial irregularity of the gas temperature field at the exit from the combustion chamber, while the circumferential irregularity at the exit from the combustion chamber increased by 1.6 %. to the sectorial unevenness 0 %. When coking the holes of the swirler cap, the value of the radial diagram at the outlet from the combustion chamber increases by 1.2%, and the value of the circumferential irregularity increases by 4%.